Catalytic Asymmetric Total Synthesis and Stereochemical Revision of Leucinostatin A: A Modulator of Tumor–Stroma Interaction. Issue 49 (10th August 2017) - Abe, Hikaru; Ouchi, Hitoshi; Sakashita, Chiharu; Kawada, Manabu; Watanabe, Takumi; Shibasaki, Masakatsu
Abstract: Total synthesis of leucinostatin A, a modulator of tumor‐stroma interactions, using asymmetric catalyses, a nitroaldol reaction, thioamide‐aldol reaction, Strecker‐type reaction, and alcoholysis of 3‐methylglutaric anhydride, is described. We demonstrated the applicability of the established catalytic asymmetric processes to the synthesis of molecules with a complex structure. Careful analysis of the NMR data, HPLC profiles, and biological activity revealed that the correct structure of leucinostatin A is the epimeric form of the reported structure; the secondary alcohol within the AHMOD residue has an R configuration. Abstract : Asymmetric catalysis : Total synthesis of leucinostatin A, a modulator of tumor‐stroma interaction was achieved by applying four catalytic asymmetric reactions. Analysis of NMR data, HPLC profiles, and biological activity revealed that the correct structure of leucinostatin A is the epimer of the reported structure.